A generic conceptual model for conducting realist qualitative research: examples from migration studies - Iosifides, T (International Migration Institute, 2011)
In this paper I propose a generic conceptual model for conducting qualitative research within the meta-theoretical premises of critical realism. I also make an effort to demonstrate the advantages of such a framework using examples from migration studies. Qualitative methods are predominately linked with meta-theoretical commitments related mainly to interpretivism, social constructionism, post-structuralism and post-modernism. Influenced by 'cultural/linguistic turn’, qualitative research has followed a path towards discursive reductionism and relativism. I contend that this path circumscribes the inherent strengths of qualitative methods and limits their explanatory power. Recently however, there have been calls for other 'turns’ which are more or less compatible with a critical realist alternative to strong social constructionism, post-structuralism and post-modernism – namely ontological, practice, complexity and materiality 'turns’. Drawing on these developments, I propose a generic model for doing qualitative research the realist way. This model is based on ways of researching real causal powers (structural, ideational and agential) and their – synchronic and diachronic – interplay, in a qualitative manner. The model views qualitative methods as powerful means for the identification of complex, causal generative mechanisms which produce certain effects and (re)connect qualitative inquiry and research with reality and, especially, with the depth investigation of its intransitive dimension. It does that by utilizing the realist concepts of 'emergence’, 'emergent properties’ and 'substantial relations’, which are predominantly concerned with qualitative changes and real connections characterized by causal powers of their own. The advantages of adopting such a model are shown by discussing its potentials for conducting qualitative migration research. More specifically, I use four examples from Greece which concern migration-related processes and phenomena. These examples concern informal immigrant employment in Athens, social mobility of immigrants in Greece, social capital and social incorporation of Albanian immigrants in Athens and the evolution of citizenship regime in the country. Through these examples I intend to demonstrate why merging realist meta-theoretical commitments with the inherent strengths of qualitative methods can result in more thorough and comprehensive understandings and explanations of migratory phenomena. The last part of the paper concerns a brief discussion of the urgent need to re-orient migration theory and research practice away from empiricist and relativist inclinations, and the central role that realist qualitative research can and should play in meeting this need.